2018
DOI: 10.1080/1331677x.2018.1441046
|View full text |Cite
|
Sign up to set email alerts
|

Backward bending structure of Phillips Curve in Japan, France, Turkey and the U.S.A.

Abstract: This work aims to analyse the cointegration and the causality relationship between inflation and unemployment by using nonlinear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…N’Guessan (2018) explored the asymmetric Phillip curve in Cote d'Ivoire using threshold cointegration methods and found that positive shocks to unemployment respond more rapidly than negative shocks and suggested the need for a particular threshold to be reached before unemployment declines rapidly. Similarly, Bildirici and Ozaksoy (2018) analyzed the same investigation in the cases of Turkey, the USA, France and Japan. The authors uncovered a weak trade-off between the variables during increasing unemployment, but it becomes stronger when the labour market is tightened.…”
Section: Literature Reviewmentioning
confidence: 99%
“…N’Guessan (2018) explored the asymmetric Phillip curve in Cote d'Ivoire using threshold cointegration methods and found that positive shocks to unemployment respond more rapidly than negative shocks and suggested the need for a particular threshold to be reached before unemployment declines rapidly. Similarly, Bildirici and Ozaksoy (2018) analyzed the same investigation in the cases of Turkey, the USA, France and Japan. The authors uncovered a weak trade-off between the variables during increasing unemployment, but it becomes stronger when the labour market is tightened.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, N'Guessan (2018) explored the non-linear Phillips curve in Cote d'Ivoire by employing threshold cointegration methods and found that positive shocks to unemployment respond more rapidly than negative shocks. Bildirici and Ozaksoy (2018) revisited the same inquiry in the cases of Turkey, the USA, France, and Japan, and the authors discovered a weak trade-off between the variables during increasing unemployment, but it became stronger when the labour market was tightened. Conversely, Bryne and Zekaite (2019) discovered that wage inflation is unresponsive to unemployment when the labour market is tight in Euro-area economies.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…They also reported an asymmetric causality between diff erent signs of the shocks, based on the Hatemi-J (2012) asymmetric causality test. Diff erently, Bildirici and Ozaksoy (2016), and Bildirici and Ozaksoy Sonustun (2018) focused on the other demand indicators in their analyses. While the former reported an asymmetry for Canada, the latter revealed an asymmetry for Japan, France, Turkey, and the USA.…”
Section: Literature Reviewmentioning
confidence: 99%